Hybrid working and organisational commitment: the role of perceived organisational support - Tresidder-Angelo, Miguel Richard (University of the Witwatersrand, Johannesburg, 2023)
Covid-19 has brought about many changes that has affected the workforce both positively and negatively. The major change brought about by Covid-19 is the alteration in the way individuals work. For many years remote working was a concept most employees had dreamed of, but through Covid-19 it became accessible to all. Now that the pandemic is at the point of phasing out and the seriousness of it has lessened, organisations are searching for a new way to maintain, motivate and increase their employees’ performance without losing the flexibility and autonomy that is afforded to remote working. This has come in the form of hybrid work which seeks to blend the benefits of remote work and the benefits of in-office work, to meet the expectations and needs of all employees and improve on both ways of work. This new concept could shape the way of work which is under-researched particularly in terms of how it will affect the employee’s attitudinal outcomes such as perceived job stress and organisational commitment. Therefore, this study explored the relationship between these two variables within a hybrid working context employees will be negative. Traditional organisational research also seemed to suggest that perceived organisational support could moderate this relationship. The aim of this study was therefore to examine the effect of job stress on organisational commitment and whether or not perceived organisational support moderates this relationship within a hybrid working context. This was done through acquiring data through purposive non-probability convenience sampling which allowed the study to obtain a sample of 106 individuals within the IT and Data Management sector. Participants were administered a self-report survey which contained three scales - Perceived Stress Scale (PSS), Organisational Commitment Questionnaire (OCQ), and Perceived Organisational Support scale (POS). A correlation coefficient test was conducted to determine the association between perceived job stress and organisational commitment and a hierarchical moderated regression was run to determine if perceived organisational support moderates this relationship within a hybrid working context. The results of this found a weak statistically negative relationship between perceived job stress and organisational commitment. Perceived organisational support was found to have a statistically non-significant moderation effect on the relationship between perceived job stress and organisational commitment.
A research project submitted in partial fulfilment of the requirements for the degree of Master of Arts (Organisational Psychology) in the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Hybrid work; Remote work; In-office work; Perceived job stress; Organisational commitment; Perceived organisational support; UCTD; SDG-8: Decent work and economic growth